Application of microwave-assisted extraction using glucose-citric acid deep eutectic solvent for enhancement of polyphenols extraction from Peperomia pellucida (L) Kunth herb - Islamudin Ahmad, Baso Didik Hikmawan, Lizma Febrina, Junaidin Junaidin, Arman Rusman, Supriatno Salam, Eko Suhartono, Yusanto Nugroho, Iskandar Iskandar, Mufrida Zein, Veri Julianto, Oky Rahmanto, Abdul Mun’im (Journal of Applied Pharmaceutical Science, 2025)
Polyphenolic compounds from Peperomia pellucida have been reported to exhibit various therapeutic applications. The level of polyphenol contained in the extract is correlated with its biological activities. A combination of natural deep eutectic solvent (NADES) and microwave-assisted extraction (MAE) is considered as a potential green method that is able to attract the target secondary metabolites. This study aims to screen the most effective NADES composition as an extraction solvent and to optimize the MAE condition on extracting polyphenols from P. pellucida herbs using Box–Behnken design with response surface methodology. The total phenolic content (TPC) was determined using a UV-Vis spectrophotometer. The combination of glucose and citric acid (1:3 w/w) yielded the highest TPC value of 114.59 mg gallic acid equivalent (GAE)/g sample among the investigated NADES compositions. The optimum conditions of MAE were attained at a microwave power of 50%, an extraction time of 5 minutes, a NADES ratio of 5:1 (w/w), and a solvent–sample ratio of 6:1 (ml/g), yielding a TPC value of 138.29 ± 2.21 mg GAE/g sample. Our findings demonstrate that glucose:citric acid-based NADES combined with MAE can be an alternative method to obtain polyphenol-rich extracts from P. pellucida.
Keywords: Microwave-assisted extraction, natural deep eutectic solvent, Peperomia pellucida (L.) Kunth, polyphenols content, response surface methodology